HUBUNGAN PENGGUNAAN TIK DENGAN KINERJA PPL DI BP3K JATI AGUNG KABUPATEN LAMPUNG SELATAN - M Nuzul Mubarokah; Dame Trully Gultom; Suarno Sadar (Lampung University, 2018)
The study aims to know the level of Information and Communication Technology (ICT) usage, the level of Extension Workers’ performance, the relation between the use of ICT and the performance of Extension Workers, and factors related to the use of ICT in Agricultural Extension Centers, Fisheries and Forestry (BP3K) Jati Agung, South Lampung District. This study was conducted at BP3K Jati Agung Regency, South Lampung District in 2017 with 17 respondents of Extension Workers. The research method used is a survey method. Methods of analysis used were descriptive analysis and Rank Spearman correlation. The results showed that Extension Workers have a high rate of ICT utilization and a high performance level. The use of ICT has a significant relationship with the performance of Extension Workers and factors related to the use of ICT are age, education, income, and cosmopolitan characteristics. Key words: extension workers, ICT, performance